Improvement of Productivity and Quality of Punching CNC - Silva Sousa, João Sinohara; Gonçalves Lins, Rômulo (Revista Ciências Exatas, 2009)
Summary In this work, it was carried through the study and the development of new forms of tools for optimization of the stamping time and improvement of the quality for punching CNC. In a first stage the stamping process was described, describing it as if it carries through and which involved phenomena in this process. Later an analysis became to determine the used techniques to solve problems faced in the assays, the job of new materials and coverings directed to the manufacture of tools, and the influence of the parameters of process (force of cut, geometry of cut in the punch and force of the press plates) in the product quality and the time of processing. The work presents, with details, the development of the solution and the results gotten through the implantation in the economic soil of plant and its results technician and. For such boarding, the case of the stamping of a perforated door was used as practical work that possesses 17000 punctures of Ø 6 mm in steel plate carbon AISI 1010. Keywords. punching CNC, reduction of production cost, improvement of productivity.